Disseminated intravascular coagulation in paediatrics. Issue 2 (18th August 2016) - Rajagopal, Revathi; Thachil, Jecko; Monagle, Paul
Abstract : Disseminated intravascular coagulation (DIC) in paediatrics is associated with significant morbidity and mortality. Although there have been several recent advances in the pathophysiology of DIC, most of these studies were done in adults. Since the haemostatic system is very different in early life and changes dramatically with age, creating a variety of challenges for the clinician, delay in the diagnosis of DIC can happen until overt DIC is evident. In this review article, we report the aetiology, pathophysiology, clinical manifestations, diagnostic tests and a management algorithm to guide paediatricians when treating patients with DIC.